Polarised neutron reflectometry studies of flux penetration in superconducting Nb - Reynolds, J; Nunez, V; Boothroyd, A; Somekh, R; Bucknall, D; Langridge, S (1997)
We have applied the technique of polarised neutron reflectometry (PNR) to investigate the magnetic held penetration in different superconducting phases of Nb, namely the Meissner state (H < H-c1), the mixed state (H-c1 < H < H-c2) and the surface superconductivity state (H-c2 < H < H-c3) around 4 K. The sample was a sputtered him of Nb with a 3 mu m thickness on a 5 mm Si crystal substrate. The measurements were carried out on the CRISP reflectometer at the ISIS facility, with field strengths between 400 and 4500 Oe. We present preliminary data for the spin-dependent reflectivity as a function of applied field. (C) 1998 Elsevier Science B.V. All rights reserved.